EMERGENCY FUND PEKERJA FREELANCE: PENGARUH LITERASI KEUANGAN DAN FINANCIAL BEHAVIOR - Eugene, Rebecca; Pertiwi, Dewi (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
This study aims to determine the influence of Literasi keuangan and Financial Behavior on the ownership of Emergency Fund Surabaya people who have Freelance work in the Digital Era. The method used is a quantitative method with the use of questionnaires as a means of data retrieval respondents. The sample used is 100 people of Surabaya who have freelance Jobs in the Digital age and are between 20-40 years old. Data analysis techniques used are logistic regression using IBM SPSS applications and the results of the analysis show that financial literacy has a significant effect on emergency fund ownership of Surabaya people who have freelance jobs in the digital era. Individuals who have a higher financial understanding and knowledge will be able to think about and recognize the need for emergency fund ownership. Financial Behavior has a significant effect on emergency fund ownership of Surabaya people who have freelance jobs in the digital era. Individuals who have good financial behavior can increase the opportunity to save for emergency fund ownership.